1978
DOI: 10.1111/j.1467-8306.1978.tb01194.x
|View full text |Cite
|
Sign up to set email alerts
|

Old Order Amish Settlement: Diffusion and Growth

Abstract: The rapid growth of the Amish population brings a concomitant growth of new settlements. This research note provides a mid-century report on new Amish settlement growth in North America, emphasizing that the vast percentage of today's extant settlements have been established in the very recent past. As settlements in-fill around decades-old settlements, spatially distinctive Amish regions are taking shape, both in states of historic settlement and neighboring states. The apparent recent success of geographical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…Currently no Old-Order exist in Europe. Persecution and political sanctions in the 17th and 18th centuries had spread European Amish families too far apart to form cohesive communities, forcing early European Amish to eventually assimilate with non-Amish (Gascho, 1937;Hostetler, 1977;Crowley, 1978;Nolt, 1992;Roth, 2002). Thus the magnitude of Amish endogamy was probably negligible in Europe compared with Amish endogamous mating in the United States.…”
Section: A Model Of (Self-)selectionmentioning
confidence: 99%
“…Currently no Old-Order exist in Europe. Persecution and political sanctions in the 17th and 18th centuries had spread European Amish families too far apart to form cohesive communities, forcing early European Amish to eventually assimilate with non-Amish (Gascho, 1937;Hostetler, 1977;Crowley, 1978;Nolt, 1992;Roth, 2002). Thus the magnitude of Amish endogamy was probably negligible in Europe compared with Amish endogamous mating in the United States.…”
Section: A Model Of (Self-)selectionmentioning
confidence: 99%
“…Yet, an Amish studies research front occurred around 1978 to 1982, and on through the 1980s, suggesting a possible future of specialized subareas. Works, such as those by Buck (1978), Cronk (1978Cronk ( / 1981, Crowley (1978), Ericksen andEricksen (1978 and, Enninger (1979), Huffines (1980), and Olshan (1981) In the opening of this article, I suggested that a field reflection must be data-driven. In previous sections, the data point and point and point to several scholars at the center of Amish studies, and these citation data are demanding an examination and assessment.…”
Section: Amish Studies Chronologicallymentioning
confidence: 99%
“…Landing (1970) called attention to the absence of Old Order Amish settlements in the U.S. South, which, at the time he wrote, consisted of a few mostly unsuccessful attempts. While the Amish had made a handful of attempts to settle the region from the end of the Civil War on (Crowley 1978), most settlements met extinction after only several years (see Luthy (1986) for detailed accounts of these settlements). The movement of the Old Order groups to a southern state goes back to attempts to create communities in Dickson County, Tennessee (Yoder 1991, 248) and Monroe County, Mississippi (Luthy 1986, 221) in the 1890s.…”
Section: Amish Population Growth and Community Formation In Kentuckymentioning
confidence: 99%